Strains for identifying and studying individual vegetative (heterokaryon) incompatibility loci in Neurospora crassa - David D. Perkins; J. F. Leslie; D. J. Jacobson (Fungal Genetics Reports, 1993)
Genetic and molecular studies of vegetative incompatibility are proceeding in several Neurospora labs. The purpose of this note is to present an expanded list of strains in the Fungal Genetics Stock Center that are potentially useful when partial diploids are employed to identify different alleles at any of the 11 known het loci of N. crassa. Some of the strains are newly deposited in FGSC. Others have previously been listed under other categories in the stock list.